3D nanostructured CuxO modified copper foam as a binder-free electrode for all-solid-state supercapacitor. Issue 22 (15th November 2021) - Li, Yanli; Jiang, Hui; Yan, Xuehua; Zhu, Yihan; Zhang, Wenjing; Zhang, Mengyang; Zhu, Wen; Javed, Muhammad Sufyan; Pan, Jianmei; Hussain, Shahid
Abstract: Copper oxides (Cux O) play an active role in the field of binder-free electrodes for supercapacitors due to their own advantages, including high theoretical capacity, non-toxicity, low cost, etc. Developing mild and cheap process to prepare Cux O nanomaterials would broad its application in supercapacitors. In this paper, copper oxide is used as an active material and copper foam (CF) is chosen as a substrate to synthesize metal oxide-based electrodes by an in-situ oxidation method. Ingeniously, the availability of copper foam has a dual nature encompassing as a collector as well as a copper source. The as-obtained Cux O/CF-60 electrode possesses an area capacitance of 354.6 mF cm −2 under 2 mA cm −2 . It also has superior cycle stability with 93.8 % of initial capacitance undergo 5000 charge-discharge cycles. Moreover, the all-solid-state asymmetric supercapacitor, combining Cux O/CF-60 and activated carbon (AC) pasted on nickel foam (NF) as the respective positive and negative electrodes, exhibits an energy density of 25 μWh cm −2 when power density reaches 3 mW cm −2 . The Cux O/CF-60//AC/NF device displays better cycling stability as 80.2 % of initial capacitance after 5000 cycles. This work provides a simple way for designing Cux O based electrodes and lays the foundation for subsequent improvements in electrochemical performance. Graphical abstract: All-solid-state asymmetric supercapacitor based on the 3D nanostructured Cux O/CF-60 electrode has good energy density and cycle stability. Image 1 Highlights: Cux O nanowires were grown on copper foam via an in-situ oxidation method. Cux O/CF was applied as a binder-free electrode for supercapacitor. Copper foam acts as a collector and provides a source of copper. Cux O/CF-60//AC/NF possesses high energy density and cycle stability.